Characterization of NA⁺-ATPase and its role in salinity tolerance of a halotolerant cyanobacterium Aphanohece halophytica - Kanteera Soontharapirakkul (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2010